2023
DOI: 10.1021/acs.iecr.3c00604
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Precious Metal Recovery from Steel Industry Slag: Recovery Strategy and Utilization

Abstract: Steel slag is a solid waste of the steel industry, produced during steel production. Three types of slag, namely electric arc furnace (EAF), basic oxygen furnace (BOF), and Linz-Donawitz processed slag (LD-slag) are the steel industry byproducts. That slag comprises precious elements including zinc (Zn), chromium (Cr), iron (Fe), nickel (Ni), silicon (Si) , aluminum (Al), and vanadium (V) and is considered a secondary source of many metals. These metal constituents can be recovered from slags by employing mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…The effect of leaching time (3–9 h) on the V leaching rate was depicted under the following conditions: L/S ratio of 20 mL·g –1 , 20 wt % sulfuric acid, and 0.3·mol L –1 oxalic acid at 140 °C (Figure ). The leaching rate of V increased continuously from 83.04 to 95.65% as the leaching time increased from 3 to 7 h and stabilized after 7 h. It indicated that enough leaching time promoted the reactions between the acid solvent and spent denitration catalyst, resulting in a higher leaching rate of V. This case might be possible because sufficient time should be spent on completely released V from the spent denitration catalyst since the V-bearing lattice structure was very stable and hard to break down. , Therefore, a leaching time of 7 h was selected by considering the maximum leaching rate of 95.65%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of leaching time (3–9 h) on the V leaching rate was depicted under the following conditions: L/S ratio of 20 mL·g –1 , 20 wt % sulfuric acid, and 0.3·mol L –1 oxalic acid at 140 °C (Figure ). The leaching rate of V increased continuously from 83.04 to 95.65% as the leaching time increased from 3 to 7 h and stabilized after 7 h. It indicated that enough leaching time promoted the reactions between the acid solvent and spent denitration catalyst, resulting in a higher leaching rate of V. This case might be possible because sufficient time should be spent on completely released V from the spent denitration catalyst since the V-bearing lattice structure was very stable and hard to break down. , Therefore, a leaching time of 7 h was selected by considering the maximum leaching rate of 95.65%.…”
Section: Resultsmentioning
confidence: 99%
“…The difficulty of releasing V from the spent denitration catalyst was determined by the interaction intensity between the leaching solvent and the mineral phases of the spent denitration catalyst. 24 In the sulfuric acid/oxalic acid combined leaching system, the crystal lattice structure of the V-bearing mineral phase was disrupted by hydrogen ions which were provided by combined acids. 20,27 In this work, the maximum concentration of hydrogen ions reached 1.99 mol•L −1 , which could strongly enhance the interaction between the combined acid and the mineral phase.…”
Section: Chemical Reaction In the Leachingmentioning
confidence: 99%
See 2 more Smart Citations
“…In our earlier investigations, highly pure alkaline lignin was successfully extracted from RGB. Such a product can be utilized in specialized aromatic chemical development, packaging, heavy metal removal, and thermal combustion. ,,, To summarize, alkaline pretreatment followed by nonionic surfactant-mediated enzymatic hydrolysis with fermentation by genetically modified microorganisms can enhance the ethanol yield and utilization of pretreatment byproducts. Thereby, such interventions can enable bioethanol production on a cost-competitive basis.…”
Section: Resultsmentioning
confidence: 99%